PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA - Amelinda, Tiara Novia; Anwar, Moch Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2021)
The development of the sharia banking industry is increasingly diverse, with many sharia products and services, with good corporate governance that is important to practice. The purpose of this study is to prove whether or not there is an effect of the implementation of Good Corporate Governance on financial performance. The type of research used is quantitative with an associative approach and secondary data. Purpose sampling technique is used as a sampling technique. Sources of data taken using secondary data are time series obtained from the company. The data analysis technique in this research uses data analysis in the form of panel data. The study found that only the audit committee board has a significant effect on financial performance. Meanwhile, other results prove that good corporate governance has a significant role in the company's financial performance.